1977
DOI: 10.1136/adc.52.9.700
|View full text |Cite
|
Sign up to set email alerts
|

Increasing breast feeding in a community.

Abstract: ResultsOver a 17-week period in the winter of 1974/75, 400 mothers were discharged from the hospital ward, of whom 172 (43%) were feeding by bottle alone, 20 (5 %) by breast with formula complements, and 208 (52 %) by breast alone (i.e. with only water complements if any). 167 of the 208 breast-feeding mothers replied to the questionnaire (a reply rate of 81 %), and are the subject of this paper. Over this 17-week period a similar incidence of breast feeding was found for the whole hospital (576 out of 1064 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

1980
1980
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 3 publications
(3 reference statements)
0
16
0
3
Order By: Relevance
“…In this study and those of Sloper et al (1977) and Martin (1978) the predominant problem experienced by the mother was the anxiety that she was not adequately nourishing her baby with breast milk. It is not possible from a study of this nature to draw any conclusions about the proportion of the mothers who did have inadequate lactation but it is well known that anxiety can inhibit the let-down reflex and impair the success of lactation (Newton & Newton, 1967).…”
Section: Discussionmentioning
confidence: 67%
“…In this study and those of Sloper et al (1977) and Martin (1978) the predominant problem experienced by the mother was the anxiety that she was not adequately nourishing her baby with breast milk. It is not possible from a study of this nature to draw any conclusions about the proportion of the mothers who did have inadequate lactation but it is well known that anxiety can inhibit the let-down reflex and impair the success of lactation (Newton & Newton, 1967).…”
Section: Discussionmentioning
confidence: 67%
“…Já foi mostrado em São Paulo, que uma campanha bem organizada através da mídia pode ter efeito mensurável e positivo na amamentação 16 . Da mesma maneira uma política de saúde encorajando o aleitamento materno na comunidade e nos hospitais, com o auxílio dos profissionais de saúde, tem mostrado uma influência positiva nos padrões de aleitamento materno 18,23 . Uma outra maneira efetiva de promover o aleitamento materno é através das visitas domiciliares pós-parto.…”
Section: Discussionunclassified
“…A follow-up study of breastfeeding in Oxford was carried out by Sloper et al 32 They observed that significantly more mothers went home breastfeeding, mothers nursed longer, and solid foods were started later when support was provided. The authors attribute this shift to the change in advice and support given in the hospital and at home visits.…”
Section: Development Of Mother Support Groupsmentioning
confidence: 99%